Media and Information Literacy of Students – Skills and Challenges in the Context of Political Preferences: The example of Poland - Barczyszyn-Madziarz, Paulina; Zieliński, Mateusz (Political Preferences, 2021)
The main purpose of this article is to present the link between the level of media and information literacy (MIL) and political preferences of Polish students based on empirical research. MIL is a key issue for today’s societies as it equips citizens with the skills needed to use various media and information channels and exercise their basic human rights. Phenomena such as post-truth, the way people are more inclined to accept arguments based on emotions and beliefs than facts, disinformation and fake news are an important context and subject of ongoing scientific discussions. Keeping in mind the limitations of self-report methods, the authors combine the elements of students’ self-assessment with the questions that test their theoretical knowledge and competences related to recognizing fake news. The research sample consists of 870 students of social sciences and journalism. The results of the research provide detailed knowledge about the level of MIL as well as political preferences of students. By that, authors hope to contribute to the global scientific discussion, offering their research conducted in the context of the declining quality of democracy in Poland.